Improving edamame yield on peat soil via Rhizobium and soil amendment applications - Rini Susana; Mahmudi; Asri Mulya Ashari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Soil amendment is a key factor in improving peat soil suitability for agriculture from the perspective of its fertility and quality. Red mud is potentially used as a peat soil ameliorant. The study aimed to evaluate red mud application as an ameliorant and application of Rhizobium on peat soil for growing edamame. The research was conducted at Tanjungpura University, Pontianak, from February to October 2024. A completely randomized design factorial was used to compile field experiments. The ameliorant factor consisted of 4 levels: control (dolomite 8 tons ha-1) and Red Mud of 10 tons ha-1, 15 tons ha-1, and 20 tons ha-1. The second factor was without and with Rhizobium. The application of Red Mud as an ameliorant increased pH, Na, and P2O5 levels and increased base saturation in peat soil. The Red Mud increased Na absorption in edamame tissues and increased pod yield. The highest edamame yield was reached with 20 tons ha-1 of red mud which was similar to with 8 tons ha-1 dolomite. Rhizobium has a role in supporting the formation of better root nodules. Keywords: crop yield; microorganisms; red mud; soil chemistry; soybean